Metabolic syndrome traits exhibit genotype-by-environment interaction in relation to socioeconomic status in the Mexican American family heart study - Diego, Vincent P.; Manusov, Eron G.; Mao, Xi; Almeida, Marcio; Peralta, Juan M.; Curran, Joanne E.; Mahaney, Michael C.; Göring, Harald; Blangero, John; Williams-Blangero, Sarah (Frontiers in Genetics, 2024)
Epidemiologic studies have identified socioeconomic status as a potent social determinant of health. Poor access to healthcare, lack of education, inadequate financial resources, experience with violence, and constant vigilance associated with low socioeconomic status explain increased morbidity and mortality in populations that live in poverty. Genotype-by-environment interaction (GxE) studies detect if genetic factors interact with the environment to produce phenotypic variation. Our results provide evidence of interactions between SES and metabolic syndrome at a molecular level in Mexican Americans living in South Texas.